Utilizing kombucha culture for coffee fermentation and biochemical characteristic analysis - Hayeong Kim; Jihyeon Jeon; Jiyeon Lee; Chaeri Song; Boncheol Gu; Nahyun Mariah Kim; Tae-hui Yang; Sejin Oh; Soochul Park; Kunal Pal; Ghahyun Jeffrey Kim; Doman Kim (Current Research in Food Science)
Coffee, an important global commodity, is grown on 10.2 million hectares in over 80 countries. Arabica coffee (Coffea arabica) is popular worldwide due to its superior flavour. As consumer interest in coffee flavour and quality continues to grow, this study aims to enhance the bioactive compounds, functionality, and sensory properties of Arabica coffee (Coffea arabica) by fermentation with black tea kombucha (K-coffee) and coffee kombucha (CK-coffee). Coffee showed a decrease in pH and an increase in titratable acidity during fermentation. The total phenolic and flavonoid content increased 1.77- and 1.95-fold in K-coffee and 2.07- and 2.60-fold in CK-coffee, respectively, after 24 h of fermentation compared to the coffee control, in which the kombucha broth was not inoculated, with an increased in trigonelline, chlorogenic acid and caffeic acid content. The caffeine content in CK-coffee increased 1.33-fold after 12 h of fermentation and remained relatively stable in K-coffee up to 24 h of fermentation compared to the coffee control. The antioxidant activity and inhibitory effect against α-glucosidase of fermented coffee increased to 2.24- and 2.40-fold after 24 h of fermentation, respectively, compared to the coffee control. Sensory evaluation highlighted noticeable differences in flavour among unfermented coffee, K-coffee, and CK-coffee with changes in volatile aroma compounds. These results support the feasibility of kombucha fermentation as a novel approach to develop specialty coffees with enhanced flavour and nutritional profiles.